PENGARUH KOMPETENSI PROFESI PMIK TERHADAP FAKTOR PENYEBAB KERUSAKAN BERKAS REKAM MEDIS DI RUMAH SAKIT X - Rita Isbandiah (POLITEKNIK PIKSI GANESHA, 2023)
This research was conducted with the aim of knowing the effect of PMIK (Medical Recorder and Health Information) professional competence on the factors causing damage to medical record files at Hospital X. The research method used is a quantitative method with a descriptive approach. Data collection techniques used are by means of observation, interviews, questionnaires and literature study. The sampling technique used a total saturation sampling technique of 19 people. Based on the results of hypothesis testing, it was obtained that the influence between variable X and variable Y was 16,048. The problems that arise are: 1) The officers are not careful and not thorough in carrying out the work of storing medical record files. 2) There is still a lack of knowledge of officers regarding the maintenance and protection of medical record files. 3) The medical record file storage rack is still made of wood so it will affect the medical record file because it is eaten by termites or rats. 4) There is no SPO (Standard Operating Procedure) for the maintenance and protection of medical record files.The suggestions given to the Hospital X include: 1) It is advisable for medical record officers at Hospital X to carry out the work of storing medical record files in a professional manner according to established standards. 2) It is advisable for the leadership of Hospital X to provide direction to the medical records manager of Hospital X to provide RMIK training in order to increase the knowledge and skills of medical record officers in medical record services. 3) We recommend that the medical records lead at Hospital X carry out Control and Monitoring (supervision and monitoring) on ​​facilities and infrastructure in medical record services in order to increase the quality and quantity of medical record service management. 4) It is recommended that the medical records manager at Hospital X make and carry out a controlling checklist (supervision checklist) for medical record officers so that officers are supervised and do their job correctly, precisely and consistently. Keywords: PMIK Professional Competency, Factors causing damage to medical record files.